2017
DOI: 10.1002/2016rs006078
|View full text |Cite
|
Sign up to set email alerts
|

A physics‐based model for the ionization of samarium by the MOSC chemical releases in the upper atmosphere

Abstract: Atomic samarium has been injected into the neutral atmosphere for production of electron clouds that modify the ionosphere. These electron clouds may be used as high‐frequency radio wave reflectors or for control of the electrodynamics of the F region. A self‐consistent model for the photochemical reactions of Samarium vapor cloud released into the upper atmosphere has been developed and compared with the Metal Oxide Space Cloud (MOSC) experimental observations. The release initially produces a dense plasma cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 24 publications
6
39
1
Order By: Relevance
“…This is further corroborated by the solar‐pumped resonance fluorescence samarium simulations by Bernhardt et al . [] and is consistent with the results from the plasma kinetic model outlined below.…”
Section: Observations and Modelingsupporting
confidence: 88%
See 2 more Smart Citations
“…This is further corroborated by the solar‐pumped resonance fluorescence samarium simulations by Bernhardt et al . [] and is consistent with the results from the plasma kinetic model outlined below.…”
Section: Observations and Modelingsupporting
confidence: 88%
“…This is in direct contrast to the work by Bernhardt et al . [], who postulate that the chemi‐ionization rate is substantially higher due to nonequilibrium population fractions of metastable states of Sm that have significantly higher rate coefficients than Sm in equilibrium thermal populations at thermospheric temperatures. The present spectroscopic analysis of the experimental data found that a simulated Sm plasma radiance spectrum at 2000 K produced a reasonable resemblance to the spectral observations between 400 and 600 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The robust description of the plasma density distribution provided by the present paper also serves as ground truth for comparison with first‐principles modeling efforts including a study of reactions of excited states by Bernhardt et al . [] and a chemical dynamic model by Holmes et al . [].…”
Section: Introductionsupporting
confidence: 81%
“…10.1002/2016RS005988 the effects of neutral cloud reaction with atomic oxygen, photo-ionization by sunlight, dissociative recombination of molecular ions, diffusive expansion, and optical emissions by solar pumped excited states. The outputs from SaReC are compared to radar, ionosonde, radio beacon, and optical spectra measured during the MOSC releases by Bernhardt et al [2017]. The main conclusion of this theoretical study is that dissociative recombination of the SmO + ion with electrons is the primary process that limits the cloud lifetime.…”
Section: Radio Sciencementioning
confidence: 99%